Status zawodowy szefów służb specjalnych. Wybrane elementy - Górnicz-Mulcahy, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
This paper analyzes the employment relationships of heads of special services appointed by the Prime Minister. The category of special services includes the Internal Security Agency, Intelligence Agency, Central Anti-Corruption Bureau, Military Counterintelligence Service, and Military IntelligenceService. The current rules regulating the appointment of central government authorities not only provide a specific procedure for the designation of heads of special services, but also describe specific requirements for aspiring candidates to perform the head of the special service function.
Keywords: szefowie służb specjalnych; status zawodowy; powołanie; prawo do wynagrodzenia